Clinical Evaluation of Effects of Local Application of Aloe vera Gel as an Adjunct to Scaling and Root Planning in Patients with Chronic Periodontitis - Anahita Ashouri Moghaddam; Golpar Radafshar; Yousef Jahandideh; Narges Kakaei (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Aloe vera gel contains various components with antibiotic and anti-inflammatory characteristics, which may have potential advantages to treat periodontal diseases. Purpose: The aim of this study was to evaluate the effects of local application of aloe vera gel as an adjunct to scaling and root planning in the treatment of patients with chronic periodontitis. Materials and Method: This single-blind clinical trial, performed in a split mouth design, was conducted on 20 patients with moderate to severe chronic periodontitis. Following a baseline examination at first day which included the assessments of plaque index (PI), gingival index (GI), and probing depth (PD); patients randomly received either SRP in one quadrant (control group), or SRP combined with aloe vera gel in another quadrant (experimental group). All cases were examined again, assessing PI, GI, and PD at 30th and 60th day. Results: There was no significant difference in PI in the three stages between control and experimental groups. In all patients, there was a significant improvement in the three stages in GI and PD for both quadrants treated only with SRP or combination of SRP and aloe vera. However, experimental group presented significantly lower GI (p= 0.0001) and PD (p= 0.009) than the control group at the end of study period. Conclusion: This study revealed that local application of aloe vera gel could be considered as an adjunctive treatment with scaling and root planning for chronic periodontitis.